The Effect Of Multimedia On Student’s Listening Comprehension At Eight Grade Of SMPN 12 Kendari - Mahadi, Yati; Hanna, Hanna; Ana, Haerun (Journal of Language Education and Educational Technology (JLEET), 2018)
The purposes of this study were 1) to investigate whether there is any significant difference of listening comprehension between students who learn listening teacher’s voice and those who learn listening by using Video at the eighth grade of SMPN 12 Kendari and 2) to investigate the students’ listening comprehension who attended the listening course by using Video at the eighth grade of SMPN 12 Kendari. Population of this study was all students at grade VIII of SMPN 12 Kendari, which consists of 7 classes; the whole classes consist of 271 students and VIII 5 as sample ofthe research. They were selected by purposive sampling. The one-group pretest-posttest design was implemented in this study. The instruments used in this study was listening test for pre-test and post-test in Experiment Class. Regarding the data analysis, mean, percentage and t-test scores for the dependent sample were employed. The result indicated that 1) there is a significant difference between students who learn listening without video and students who learn listening with video at the eighth grade of SMPN 12 Kendari and 2) teach Using Video on Listening Comprehension affect to Students’ listening skill at Grade Eight of SMPN 12 Kendari